Numerical investigation of the effect of spoilers configuration on wake vortex - Omar, Ashraf Ali; Asrar, Waqar ([s.n], 2012)
A numerical investigation was undertaken to study the aerodynamic characteristics of wake vortices generated from an aircraft during taking-off or landing, and thus exploring the possible techniques of reducing hazard imposed to the following aircraft by means of passive wake vortex alleviation. An initial study has been carried out on passive wake vortex alleviation by using delta wing (DW) as an add-on device. Simulations were performed using RANS turbulence model. The results were obtained and quantified at measurement section locations downstream, of x/c=1.359 and x/c=3.418 measured from leading edge point of the model Although the simulations capture vortex roll-up trends, the size of the vortex is not predicted correctly by RANS turbulence model. Overall, it can be concluded from the results that the wake vortex generated from DW exhibit high tangential velocity magnitude and circulation at a particular angle of attack (AOA) between 20º to 30º. Subsequently, a broader investigation of another passive wake vortex alleviation technique was performed to study the potential of differential spoiler setting (DSS) of a scaled, half-model aircraft in alleviating the rolling moment induced on the following aircraft. The model was simulated under high lift configuration (HLC) condition, using inherently unsteady technique adopted in LES turbulence model, for two outboard loading cases and two inboard loading cases, in addition to the baseline configuration case. The study has covered near-wake field and extended near-wake field by taking seven measurement section planes at x/b=0.345, x/b=0.444, x/b=0.658, x/b=1.076, x/b=1.794, x/b=2.691 and x/b=4.484. Comparison between numerical simulations and experimental results has shown good agreement in term of lift coefficient for all cases, and fairly acceptable agreement in term of maximum cross-flow velocity, maximum normalized total circulation and maximum induced rolling moment. However, there were some occasions where the comparison is not so good. For instance, the difference error has risen up to 40.3% in term of maximum normalized cross-flow velocity for baseline configuration. Evaluation of the results has showed promising outcomes for the inboard loading cases compared to the outboard loading cases. The interaction between spoilers’ wake and outboard flap tip vortex of the inboard loading cases has reduced the tangential velocity magnitude and circulation of the wing tip vortex, and delayed vortex merging to farther distance downstream. This conclusion justifies the DSS’s capabilities in wake vortex alleviation. Therefore, DSS can be considered as one of the promising techniques that can be used commercially in the future.